An ecoregional perspective on malnutrition - Sharma, Manohar; Brown, Lynn R.; Qureshi, Aamir; Garcia, Marito (International Food Policy Research Institute, 1995)
In agrarian developing countries the natural environment is a key determinant of both poverty and nutritional status. Climate, terrain, and soil characteristics drive the agricultural system, determining in large part cropping patterns, choice of crops, yield rates, and overall productivity levels. The human resources crucial to agricultural productivity are also influenced by the natural environment. The Consultative Group on International Agricultural Research (CGIAR) is placing priority on developing a concept of ecoregional zones based on the premise that agroecological conditions largely determine the production potential and the size of population that an area can support in the developing world. Understanding the ecoregional dimensions of poverty and malnutrition potentially could be a major step forward in alleviating poverty sustainably by the year 2020 because it may help to target scarce resources more effectively. There are clearly discernible links between the natural environment, agricultural productivity, health, and nutritional status. Use of an ecoregional dimension to explore the incidence of malnutrition exploits these linkages. Analysis at the ecoregional level suggests that targeting of scarce resources to address the problems of poverty and malnutrition could potentially be improved by 2020 by taking into consideration these linkages between ecoregional characteristics and poverty.